2017
DOI: 10.1590/1517-869220172303158272
|View full text |Cite
|
Sign up to set email alerts
|

Técnicas de aterrissagem afetam o desempenho e estresse mecânico durante Drop Jump

Abstract: Introdução: O drop jump é utilizado para melhorar da potência dos membros inferiores. Mantendo-se a altura de queda constante, a variação da técnica de aterrissagem pode alterar o desempenho e as características mecânicas do salto. Objetivo: Avaliar os efeitos da alteração da técnica de aterrisagem no desempenho e na força de reação do componente vertical do solo após drop jump. Métodos: Vinte e cinco homens saudáveis e fisicamente ativos (idade: 26±8 anos, massa corporal total: 75±10 kg, altura: 175±10 cm) re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…Guy-Cherry et al found that vGRF of the knee extension group was maximum by investigating 5 DJs at 0.4 m, and its RSI was significantly higher than that of the knee flexion group [ 35 ]. Marchetti et al showed that the landing time of the BDJ at 40 cm was shorter than the 90° knee flexion and 135° knee flexion [ 36 ]. Struzik et al suggested that the RSI of the BDJ group was higher than that of the CDJ group at 30 cm, 45 cm, and 60 cm [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Guy-Cherry et al found that vGRF of the knee extension group was maximum by investigating 5 DJs at 0.4 m, and its RSI was significantly higher than that of the knee flexion group [ 35 ]. Marchetti et al showed that the landing time of the BDJ at 40 cm was shorter than the 90° knee flexion and 135° knee flexion [ 36 ]. Struzik et al suggested that the RSI of the BDJ group was higher than that of the CDJ group at 30 cm, 45 cm, and 60 cm [ 37 ].…”
Section: Discussionmentioning
confidence: 99%